Combined effects of LED lights and chicken manure on Neochloris oleoabundans growth. (November 2017) - Altunoz, Meltem; Pirrotta, Onofrio; Forti, Luca; Allesina, Giulio; Pedrazzi, Simone; Obali, Olcay; Tartarini, Paolo; Arru, Laura
Highlights: Chicken manure is used as microalgal growth medium for Neochloris oleoabundans . Different wavelengths of LED such as white, blue and blue-red combined are tested. The basic design of a chicken-manure-fed photobioreactor is defined. Abstract: In this study a photobioreactor prototype is presented for the culture growth of microalgae model organism Neochloris oleoabundans by using chicken manure waste as feedstock along with the optimum combination of led light wavelengths and light intensity. Particularly interesting results are observed on the strains fed by chicken manure medium under the proper combination of red and blue LED light illumination, the microalgal growth resulted comparable with the strains fed by the costly commercial microalgal growth medium (BG 11 medium). Cell concentration, optical density, growth rate, cell size, total lipid and photosynthetic pigment content have been monitored during a time-course experiment. The data suggest that there are difficulties due to white light diffusion into the dark chicken medium, which leads to a generally lower intensity scattered along all wavelengths; blue or combined red and blue lights resulted in a higher irradiation density, affecting microalgae cell growth.